Peran Perempuan dalam Kepemimpinan: Perspektif Hadis dan Realitas Kontemporer - Jainah , Jainah; Monady, Hanief; Sa’adah, Nismah (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
In several Muslim societies‟ recent history, women‟s leadership has been a contentious topic. The majority of Muslim scholars have rejected it due to its crippling effects, however others have accepted it as a way to meet community needs in a contemporary setting. Because of the lack of a clear direction about the state‟s leadership and the government‟s high position, this topic is contentious and prone to conflict. In light of this, it is necessary to examine Muslim leadership in the perspective of modern Muslim scholars. The concept, a brief history, the opinions of modern Islamic scholars, and the significance of Muslim women‟s leadership within the framework of modern Islamic thought are all covered in this paper. M. Quraish Shihab and KH. Husein Muhammad‟s ideas on women‟s leadership are compared and contrasted, and they are founded on arguments and modern interpretations of the Qur‟an and the Sunnah. This essay comes to the conclusion that, in light of Islamic (Sharia) law, modern Muslim scholars are unable to offer a convincing and useful justification for women‟s leadership. While it‟s true that Islam doesn‟t offer any concrete rules, in actuality, it gives women a wide range of opportunities to work in the public sector. This is due to the fact that men and women were formed in equal roles and have equal access to opportunities in areas such as employment and leadership roles. Keyword: Women, Leadership, Hadith, Contemporary Reality.